Laser Surface Texturing of Cutting Tools for Improving the Machining of Ti6Al4V: A Review - Javier Garcia-Fernandez; Jorge Salguero; Moises Batista; Juan Manuel Vazquez-Martinez; Irene Del Sol (Metals)
The machining of titanium alloys, particularly Ti6Al4V, presents a significant challenge in manufacturing engineering. Its high strength, low thermal conductivity and high chemical reactivity make Ti6Al4V a hard-to-machine material. However, the machining process is critical for aerospace and biomedical industries. The rapid wear and short lifetime of cutting tools are the main limitations in Ti6Al4V machining, leading to a large increase in manufacturing costs and compromising the surface quality of machined components. Faced with this problem, the texturing of cutting tools, especially through laser-based techniques, has gained considerable attention in the last decade due to improvement of the tribological properties of textured surfaces. Laser Surface Texturing (LST) has emerged as a promising technique to improve the tribological performance of cutting tools by enabling the creation of precise surface structures. Building on prior research, this review provides a comprehensive overview of the most recent research on this topic, summarizing key findings and outcomes from various investigations.